2009
DOI: 10.2965/jwet.2009.91
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage and resistance to uprooting forces of eelgrass (Zostera marina L.) shoots planted in slag substrates

Abstract: Different types of slag (air-cooled, granulated and carbonated granulated slag) were employed as basal media of eelgrass, Zostera marina L. We investigated how factors such as slag type, particle size and sedimentation of fine particles affected anchorage of eelgrass to the substrates. It was found that eelgrass planted in slag substrates could endure current velocity of 10 to 50 cm s -1 . Thus, slag substrates can adequately support and anchor the eelgrass plants even during severe current flow (50 cm s -1 ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Rhizome to root ratio in exposed conditions seagrass indicated they invested greater quantities in rhizome than root biomass compared to sheltered conditions. Seagrass response to disturbance in sandy substrates was to produce more rhizomes for anchorage as in agreement with other studies (Hemminga and Duarte, 2000;Hizon-Fradejas et al, 2009). A similar pattern was also seen for depth across sites.…”
Section: Multi Effects On Seagrass Biomass Carbon Stockssupporting
confidence: 91%
“…Rhizome to root ratio in exposed conditions seagrass indicated they invested greater quantities in rhizome than root biomass compared to sheltered conditions. Seagrass response to disturbance in sandy substrates was to produce more rhizomes for anchorage as in agreement with other studies (Hemminga and Duarte, 2000;Hizon-Fradejas et al, 2009). A similar pattern was also seen for depth across sites.…”
Section: Multi Effects On Seagrass Biomass Carbon Stockssupporting
confidence: 91%
“…The culture methods developed for Z. marina along the mid-Atlantic coast of North America have the potential to be used for the restoration of Z. marina in other regions and for other species. For example, Z. marina is the focus of seagrass restoration projects in Japan (Hizon-Fradejas et al 2009), where it has a similar reproductive phenology and growth cycle to what we observed (Abe et al 2008). Zostera species are found on every continent (Green & Short 2003), and in several species, seed germination can also be promoted by changes in temperature, salinity, and/or oxygen conditions (Hootsmans et al 1987;Conacher et al 1994;Brenchley & Probert 1998;Orth et al 2000;Abe et al 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Zostera marina (eelgrass) has been the focus of most of the submerged aquatic vegetation (SAV) restoration activities along temperate coasts of North America (Fonseca et al 1998), Europe (Christensen et al 2004; van Katwijk et al 2009), and the northwest Pacific (Park & Lee 2007; Hizon‐Fradejas et al 2009). This is also true for the Chesapeake Bay on the mid‐Atlantic coast of North America where this species has historically dominated in the higher salinity areas, but has declined during the last century as a result of disease and poor water quality (Kemp et al 1983; Orth & Moore 1983 a ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the dynamic forces produced by waves affect the physical stability of the organisms (Denny et al, 1998;Gaylord et al, 2001;Utter and Denny, 1996). In our previous study with slag substrates, we found that the force needed to uproot eelgrass plants was higher for transplants in fine particles than in coarse particles (Hizon-Fradejas et al, 2009b). The purpose of this study is to evaluate the effect of mixtures of MS as the basal material and DS or FA as the silt-clay component on the anchorage ability of eelgrass roots.…”
Section: Introductionmentioning
confidence: 97%
“…Approximately 24 million tonnes of blast furnace slag and 10 million tonnes of FA are produced each year in Japan (Nippon Slag Association, 2011;Tanaka et al, 2010), and are thus available in sufficient quantity should they prove desirable materials for eelgrass bed restoration. Dredged sediment (DS) was also considered and evaluated as a silt-clay source (Hizon-Fradejas et al, 2009b.…”
Section: Introductionmentioning
confidence: 99%